The Effectiveness of Using Mobile Phones in Developing English Writing Skills by Yemeni EFL University Students - Alsoofi, Naziha; Al-Mekhlafi, Mohammed Abdu Ahmed; Al-Qubati , Helal Ahmed Ali (International Journal of Language and Literary Studies, 2025)
This research aimed to investigate the effectiveness of using mobile phones in developing English writing skills by Yemeni EFL university students. The researcher employed a quasi-experimental method. The sample of this study was 50 EFL students who were selected from level two at the Department of English, Faculty of Education, Sana'a University during the academic year 2023-2024. The sample was divided into two groups. The control group consisted of (25) students taught by the traditional way while the experimental group consisted of (25) students taught through using mobile phones (Google Classroom App). The data were collected through a writing test whose results showed a large effect for using the mobile phones to improve the students' writing skills. The results of this study showed that there were statistically significant differences at the 0.05 level between the mean scores in the pre-test and post-test of the experimental group in favor of the post test. In addition, the results showed that there were statistically significant differences at the 0.05 level between the mean scores in the post-test of the experimental group taught the writing skills using mobile phones and the control one taught the writing skills by the traditional method in favor of the experimental group. It can be concluded that the students of the experimental group got significant effect and improvement in the writing skills after using mobile phones. The current study ends with some educational implications, recommendations and suggestions for future research studies.